The Relationship Between Debt, Default, and Receivables in Contract Law in Indonesia - Januar, Inri; Santoso, Budi; Sulistyarini, Rachmi; Qurbani , Indah Dwi (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
Treaty law recognizes the terms debt and receivables, but in the legal regulations of agreements or beyond it, it turns out that what is meant by debt and receivables is very limited in its explanation. Likewise, default whose definition appears only limited to the opinions of experts. Regulation will be very important because debts, receivables and defaults have legal consequences for creditors or debtors. Thus, it is very necessary to include the definition of debt, receivables and defaults in laws and regulations to provide certainty and legal protection for the parties to the engagement, especially the law of agreements. The type of research used is normative juridical research using primary legal materials, namely laws and regulations, secondary, namely books by law scholars and tertiary materials in the form of dictionaries. The approach used is a conceptual approach and a legislative approach. From the results of the study, there is a void in norms regarding receivables. Receivables in general cannot arise without obligation, for certain conditions receivables may arise without prior obligation. Receivables are not only the opposite of the word debt. Receivables are the right to sue given by law. In this case, receivables can be interpreted as protection provided by the state to the subject in the law of the agreement. Default is not the same as debt and a defaulter cannot have receivables.